Effects of Uncertain and Nonstationary Parameters Upon Capital Market Equilibrium Conditions - Barry, Christopher B. (Journal of Financial and Quantitative Analysis, 1978)
Christopher B. Barry, Effects of Uncertain and Nonstationary Parameters Upon Capital Market Equilibrium Conditions, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 3 (Sep., 1978), pp. 419-433